2011
DOI: 10.1159/000335068
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Survival of Diffuse Coronary Artery Disease Patients following Coronary Artery Reconstruction with the Internal Thoracic Artery

Abstract: Objective: Diffuse coronary artery disease makes cardiac surgeons hesitant regarding whether coronary artery bypass grafting (CABG) surgery is feasible or not. Coronary artery reconstruction using the internal thoracic artery (ITA) allows bypassing of coronary arteries with diffuse atheromatous plaques without systematically resorting to endarterectomy. The aim of the present study was to evaluate the medium-term results of coronary artery reconstruction. Methods: All patients undergoing coronary artery recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(31 reference statements)
0
9
0
2
Order By: Relevance
“…В среднем, по данным литературы, госпитальная летальность находится в пределах 2,0-6,5% [2,4,5]. Этот показатель выше, чем при обычном АКШ, однако многие авторы отмечают, что связано это, прежде всего, с сопутствующей патологией и тяжёлым исходным состоянием пациентов, а не с самой операцией [2,6].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…В среднем, по данным литературы, госпитальная летальность находится в пределах 2,0-6,5% [2,4,5]. Этот показатель выше, чем при обычном АКШ, однако многие авторы отмечают, что связано это, прежде всего, с сопутствующей патологией и тяжёлым исходным состоянием пациентов, а не с самой операцией [2,6].…”
Section: Discussionunclassified
“…По различным оценкам, его частота достигает 1,5-15% [2,3,6]. При ЭАЭ из нескольких бассейнов риск увеличивается [8].…”
Section: Discussionunclassified
“…In a recent issue of Cardiology , Khalifa et al [1] reported the medium-term clinical results of a cohort of 233 patients submitted to surgical left anterior descending artery (LAD) reconstruction and bypass using the internal thoracic artery. …”
Section: Introductionmentioning
confidence: 99%
“…From a surgical standpoint, the procedure described by Khalifa et al [1] requires considerable expertise and is certainly more challenging compared to conventional coronary surgery. This is reflected by the longer cardiopulmonary bypass and cross-clamp times, although with the modern protocols for myocardial protection and cardiopulmonary bypass management these issues are of relatively minor concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation